The Correlation Between Erythrocyte Sedimentation Rate (ESR) and Platelet Count with Fever Levels in Pediatric Patients with Typhoid Fever at Methodist General Hospital Medan in 2023 - Donitha Rorescki Simanjuntak; Alexander P. Marpaung; Salomo G. U Simanjuntak; Dwi Lunarta D.S. Siahaan; Lesmana Syahrir (Universitas Methodist Indonesia, 2025)
Background : typhoid fever is an acute febrile disease caused bySalmonella typhi bacterial infection and can be caused also by SalmonellaParatyphoid a, Salmonella Typhi B, and Salmonella Paratyphoid C.Found endotoxin in bacterial polysaccharide S.typhi stimulate theproduction of cytokines and cause systemic symptoms such as fever,vomiting, headache, diarrhea, constipation. Endotoxins induce changes inbone marrow cells and affect ESR values and platelet counts. At the levelof fever, there are 3 levels of temperature increase, namely febris,subfebris and hyperpyrexia. Objective: this study was conducted todetermine the relationship of the value of ESR and platelet count to feverlevels in pediatric patients with typhoid fever.Method: research method with observational analytical measurementthrough retrospective approach with cross sectional design, usingsecondary data in medical records, researchers make observations ormeasurements of variables at a particular time.Results : In the analysis there is a significant relationship between thevalue of the LED with fever level with a value of p=0.039 and there is norelationship between platelet count with fever level with a value ofp=0.089.Conclusion: there is a relationship between the value of LED with fever level and there is no relationship between platelet count with fever levelwith a value of p= 0.089.